Question
upstudy study bank question image url

\[ \begin{array}{l} =2^{6} \cdot 3^{1} \\ =192 \end{array} \] \[ \begin{array}{l} =\frac{2^{x}(3)}{3.2^{x}} \\ =1 \end{array} \] EXERCISE 1 Simplify the expressions without using a calculator: (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) \( 2 \frac{2\left(2 a^{4}\right)^{3}}{16 a^{12}} \) (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) \( 4 \quad \frac{3 a^{3} \times 5 a^{5}}{\left(5 a^{3}\right)^{2}} \) \( 5 p^{x-1} p^{x+1} \) (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) \( 7 \quad 16^{4 x} \div 4^{2 x} \) (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) 9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) \( 10 \frac{3^{x}+3^{x+1}}{8} \) Negative exponents and the meaning of \( a^{0} \) \( a^{0}=1 \) because \( 5 \div 5=1 \) and \( 5^{1} \div 5^{1}=\frac{5^{1}}{5^{1}}=5^{1-1}=5^{0}=1 \quad \) Using Law 2 For example: \( (2 x)^{0}=1 ; 2 x^{0}=2 \times 1=2 ;(a+b)^{0}=1 \)

Ask by Hodges Bolton. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

1. \( \frac{4}{5} a^{8} b^{14} \) 2. \( 2 \) 3. \( 3 a^{2} \) 4. \( \frac{3}{5} a^{2} \) 5. \( p^{2x} \) 6. \( -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \) 7. \( 4^{6x} \) 8. \( \frac{8}{27} \) 9. \( 2^{1010} \cdot 5^{1011} \) 10. \( \frac{3^{x}}{2} \)

Solution

Let's simplify each expression step by step. ### (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) First, we can multiply the coefficients and the variables separately: \[ \frac{1}{4} \times \frac{16}{5} = \frac{16}{20} = \frac{4}{5} \] Now for the variables: \[ a^{5} \times a^{3} = a^{5+3} = a^{8} \] \[ b^{12} \times b^{2} = b^{12+2} = b^{14} \] Combining these results, we have: \[ \frac{4}{5} a^{8} b^{14} \] ### (2) \( 2 \frac{2(2 a^{4})^{3}}{16 a^{12}} \) First, simplify the expression inside the parentheses: \[ (2 a^{4})^{3} = 2^{3} (a^{4})^{3} = 8 a^{12} \] Now substitute this back into the expression: \[ 2 \frac{2 \cdot 8 a^{12}}{16 a^{12}} = 2 \frac{16 a^{12}}{16 a^{12}} = 2 \cdot 1 = 2 \] ### (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) Combine the terms in the numerator: \[ 6 a^{4} + 9 a^{4} = 15 a^{4} \] Now simplify: \[ \frac{15 a^{4}}{5 a^{2}} = 3 a^{4-2} = 3 a^{2} \] ### (4) \( \frac{3 a^{3} \times 5 a^{5}}{(5 a^{3})^{2}} \) First, simplify the denominator: \[ (5 a^{3})^{2} = 25 a^{6} \] Now simplify the numerator: \[ 3 a^{3} \times 5 a^{5} = 15 a^{3+5} = 15 a^{8} \] Now combine: \[ \frac{15 a^{8}}{25 a^{6}} = \frac{15}{25} a^{8-6} = \frac{3}{5} a^{2} \] ### (5) \( p^{x-1} p^{x+1} \) Using the property of exponents: \[ p^{(x-1) + (x+1)} = p^{2x} \] ### (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) First, expand the square: \[ (-4 a^{2} + b^{3})^{2} = 16 a^{4} - 8 a^{2} b^{3} + b^{6} \] Now multiply by \(-2\): \[ -2(16 a^{4} - 8 a^{2} b^{3} + b^{6}) = -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \] ### (7) \( 16^{4 x} \div 4^{2 x} \) Convert to the same base: \[ 16 = 4^{2} \Rightarrow 16^{4x} = (4^{2})^{4x} = 4^{8x} \] Now simplify: \[ \frac{4^{8x}}{4^{2x}} = 4^{8x - 2x} = 4^{6x} \] ### (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) Convert to prime bases: \[ 12 = 2^{2} \cdot 3^{1}, \quad 27 = 3^{3}, \quad 18 = 2^{1} \cdot 3^{2} \] Now express each term: \[ 12^{x+1} = (2^{2} \cdot 3^{1})^{x+1} = 2^{2(x+1)} \cdot 3^{x+1} \] \[ 27^{x-2} = (3^{3})^{x-2} = 3^{3(x-2)} = 3^{3x - 6} \] \[ 18^{2x-1} = (2^{1} \cdot 3^{2})^{2x-1} = 2^{2x-1} \cdot 3^{2(2x-1)} = 2^{2x-1} \cdot 3^{4x-2} \] Now substitute back: \[ \frac{2^{2(x+1)} \cdot 3^{x+1} \cdot 3^{3x-6}}{2^{2x-1} \cdot 3^{4x-2}} = \frac{2^{2x+2} \cdot 3^{4x-5}}{2^{2x-1} \cdot 3^{4x-2}} \] Now simplify: \[ = 2^{(2x+2) - (2x-1)} \cdot 3^{(4x-5) - (4x-2)} = 2^{3} \cdot 3^{-3} = \frac{8}{27} \] ### (9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) Convert \(10^{1000}\): \[ 10^{1000} = (2 \cdot 5)^{1000} = 2^{1000} \cdot 5^{1000} \] Now simplify: \[ \frac{2^{2010} \cdot 5^{2011}}{2^{1000} \cdot 5^{1000}} = 2^{2010-1000} \cdot 5^{2011-1000} = 2^{1010} \cdot 5^{1011} \] ### (10) \( \frac{3^{x}+3^{x+1}}{8} \) Factor out \(3^{x}\): \[ = \frac{3^{x}(1 + 3)}{8} = \frac{3^{x} \cdot 4}{8} = \frac{3^{x}}{2} \] ### Summary of Results 1. \( \frac{4}{5} a^{8}

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

Did you know that the concept of exponents dates back to ancient civilizations? The Egyptians and Babylonians used rudimentary forms of exponentiation to solve problems involving area and volume. Over time, mathematicians developed more formal rules, culminating in the laws of exponents we use today, allowing complex expressions to be simplified cleanly and efficiently. When simplifying expressions, one common pitfall is forgetting the rules for negative exponents. Remember, \( a^{-n} = \frac{1}{a^{n}} \) and treat them carefully. Another mistake is misapplying the laws of exponents while combining like bases—always ensure that you add or subtract exponents correctly! Keeping these in mind can make simplifying expressions feel almost like a party trick!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy